Social Inequality in a Developed Nation: A Global Humanitarian Perspective in the Film Manbiki Kazoku (Shoplifters) - Hidayat, Syifa Amelia; Putri, Sylvia Octa; Haryanti, Pitri; Adibowo, Rino (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The current research seeks to identify the issues of social inequalities and human security crisis highlighted in Hirokazu Kore-eda’s movie, Manbiki Kazoku (Shoplifters). Despite Japan being renowned for its top welfare systems, this paper will examine whether the movie offers an insight into people who are deprived of their basic human rights due to their socio-economic status, which falls below the poverty line in urban areas. Following the qualitative descriptive research design, this paper applies a combined methodology from Cultural Studies and Human Security theories within the field of International Relations. This paper demonstrates that Shoplifters provides deep insights into the problem of invisibility of poverty and the state’s inability to ensure the fulfillment of the citizens’ fundamental rights. As seen in the survival tactics adopted by the Shibata family members (including the lack of education), there is a considerable mismatch between the Sustainable Development Goals (SDG 1; SDG 4; SDG 10). The inference from this study is that prosperity on the macroeconomic level within the Global North does not equate to the securing of human security among the populace at the grass roots level. This study highlights the importance of recognizing undocumented individuals and advocates the use of cultural artifacts as valid instruments within the field of Development Studies